ISOLATION AND DNA FINGERPRINTING ANALYSIS OF BACTERIOPHAGES SPECIFIC TO RALSTONIA SOLANACEARUM - MAKARI HANUMANTHAPPA K; MAKARI HANUMANTHAPPA K; PALANISWAMY M; ANGAYARKANNI J; VINAY SUVARNA M N (International Journal of Pharma and Bio Sciences, 2014)
The aim of this research work was to analyze the genetic diversity of the lytic bacteriophages isolated against phytopathogenic Ralstonia solanacearum. The 16S rRNA sequence analysis was used for the identification of the bacteria. Four lytic phages: fHMPM12, fHMPMA12,fHMPMB12 and fHMPMC12 specific to R. solanacearum were isolated from sewage sample. The phage fHMPM12 was found more stable in all temperature ranges. Transmission electron microscopic (TEM) analysis was used to determine the morphology of the phages. Electronic microscopic images of phages revealed that bacteriophages have possessed icosahedral head shape of 45-55 nm in diameter and a non-contractile tail of 210-235 nm in length, these morphological similarities of the phages were represents the family Siphoviridae. The RAPD PCR technique was employed with primers OPC04 sequence 5′-CCGCATCTAC-3′ and OPC05 sequence 5′-GATGACCGCC-3′ series. The genomic fingerprinting of all the four phages by RAPD PCR revealed the distinct banding patterns. The findings of the study support the use of RAPD PCR technique for the quick typing of phage isolates and assessment of genetic diversity.